A STRUCTURALIST APPROACH TO EARNEST HEMINGWAYâS FOR WHOM THE BELL TOLLS - Indri, Kustantinah; Festi, Karima Himatu (ETERNAL, 2010)
Abstract Â  This research is undergone in order to look for surface manifestation and to find out deep structure of Earnest Hemingwayâs For Whom the Bell Tolls. To convey the novel structure, the particular goals reached in this research is to analyze the plot and structure that relate to conflict in the story. The method used in this research is qualitative that use structuralist approach. The results of this research are (1) it is obviously clear that the surface structure of For Whom the Bell Tolls is novel (its genre). This novel can be categorized in tragedy since it has catastrophe in the end of the story; (2) A deep structure lies on its plot structure that has five stages. The incentive moment of the novel starts at Robert Jordan came to Spain in 1937 to help the Republican in the war, travels behind enemy lines to work with Spanish guerrilla fighters hiding in the mountains. The rising action starts when Pablo (the head of the guerillas) refused to help Robert to explode the bridge since he thought that job endangered their life. Troubles come to Jordan, but he determines to explode the bridge becoming the climax. The falling action follows the explosion of the bridge by Jordan and the guerrillas and the death of some guerrilla fighters. Finally, The death of Robert Jordan becomes the catastrophe of the story. Â  Â  Keywords: Â  structuralism, plot, structure, and conflict.